Occurrence of the isopod, Norileca indica (Isopoda: Cymothoidae) on bigeye scad, Selar crumenophthalmus (Bloch) off Mumbai coast, India - Neeraja, Tambireddy; Tripathi, Gayatri; Shameem, Ummey (Indian Journal of Fisheries, 2013)
Kalbasu, Labeo calbasu (Hamilton) reared under natural conditions were examined for variation in selected innate immune parameters during three different seasons of a year. The reference ranges for the innate immune parameters viz.. lysozyme, peroxidase, ceruloplasmin, antiprotease and alternative complement haemolytic activitiy, superoxide production by phagocytes, total protein level of serum, haemolysin, haemagglutination and bacterial agglutination titre and blood glucose level of this species were established. The seasonal and sex-related variations in some of the parameters in this fish were also evaluated. Significant seasonal variations in peroxidase activity, superoxide production by phagocytes, alternative complement activity and haemolysin titre were observed. In contrast, serum lysozyme activity and blood glucose level did not show significant seasonal variations. Males had higher haemagglutination titre in the breeding season when compared to females.